PERBANDINAGN TES BERBASIS KOMPUTER DAN TES KERTAS PENSIL DALAM PENDIDIKAN - Sri Hartini (Joglo, 2011)
ABSTRACT The test is one of import functions of educational system. It is used to give many information for students, teachers, parents and decision makers. Based on that information they make many decisions better. In one hand, it can help them to make decision about everything are related learning and education as to decide a good class for the student, possibility to continue on learning and the other hand to give many feedback about effectively learning and educational process. Now, test paper pencil are based on Behaviorism Theory. Students are responded to stimulation from environment but really they need test more than just can make to relate stimulus and respon (9S-R Bond ). They need to improve how can make cognitive structure, how can use their knowledge to applied and how can do to solve many problems that they’re faund. We need Cognitive Theory beside Behaviorism Theory. Test based on computer ( TBoC ) are improved by the Cognitive Theory. It give a new perspective to the teacher and the student. It has values added more than test based on paper-pencil (TBoPP). There are many indicators of values added of TBoC: 1. To make a good feeling of the testee.2. Mean Score of Adaptif Test is Higher more than Paper-Pencil Test.3. Score accuration with computer is higher more than human manual procedures.4. Computer can make complicated tasks to simple tasks. Test Based on Computer has limited too beside values added, therefore we have to remember many condition for successing. The conditions we need are : Computer knowledge, We can’t effectively on applied Test based on Computer if without three conditions above, Keywords : Comparations, Test Based on Computer, Test based on Paper Pencil, Behaviorism Theory, Cognitive Theory.